Faktor-faktor yang Berhubungan dengan Tingkat Kecemasan Pre Kateterisasi Jantung Pasien SKA - Devi Listiana (CHMK NURSING SCIENTIFIC JOURNAL, 2019)
ABSTRACT The purpose of this study is to determine the Factors who associated with Level of Anxiety pre Cardiac Catheterization on Patient with SKA in Cath-Lab Ward RSUD dr. M. Yunus Bengkulu in 2018. This study used cross sectional design. Population in this study were all patient with SKA who were doing treatment of Cardiac Catheterization in Cath-Lab Ward RSUD dr. M. Yunus Bengkulu in 2018. Sample in this study were all patient diagnozed with SKA who were doing treatment of Cardiac Catheterization in Cath-Lab Ward RSUD dr. M. Yunus Bengkulu. Sampling technique in this study used accidental sampling where subject choosed on the time of study conducting. The result of this study showed: (1) there is no significant relationship between age and Level of Anxiety pre Cardiac Catheterization on Patient with SKA (2) there is significant relationship between gender and Level of Anxiety pre Cardiac Catheterization on Patient with SKA with weak category relationship. (3) there is significant relationship between education and Level of Anxiety pre Cardiac Catheterization on Patient with SKA with weak category relationship. It is expected that health workers in hospitals, especially nurses, can be able to measure the patient's anxiety level so that they can provide appropriate care, and can provide counseling, information and education needed by patients with anxiety disorders to help patients overcome their anxieties. Keywords: Age, Gender, Education, Level of Anxiety pre Cardiac Catheterization